2015
DOI: 10.1080/14719037.2015.1066418
|View full text |Cite
|
Sign up to set email alerts
|

Policy Role of Social Media in Developing Public Trust: Twitter communication with government leaders

Abstract: Citizens' trust in a government is critical when the government utilizes Twitter to communicate with the public. This research collected 398 questionnaire samples from Korean citizens who communicate with a central government department via Twitter and employed a structured equation analysis. The study discovered that tweets coming from a leading (or an executive) government officer (e.g., a minister) played mediation role in increasing citizens' perception of credibility in governmental Twitter feed. Furtherm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(32 citation statements)
references
References 47 publications
1
31
0
Order By: Relevance
“…The interviewees corroborate the literature [20,30,31,[43][44][45][46][47][48][49] that points out the possibility of using social media to increase citizens' satisfaction in government. The increase comes from receiving and monitoring citizens' demands by government agents.…”
Section: E-participation Targetssupporting
confidence: 76%
“…The interviewees corroborate the literature [20,30,31,[43][44][45][46][47][48][49] that points out the possibility of using social media to increase citizens' satisfaction in government. The increase comes from receiving and monitoring citizens' demands by government agents.…”
Section: E-participation Targetssupporting
confidence: 76%
“…Researches show that in the past few years, a number of topical research trends have emerged with application of Web 2.0 technologies in the e-government (Alguliyev & Yusifov, 2018;Alotaibi, Ramachandran, et al, 2016;Chun et al, 2010, Parveche & Sachs, 2010Rodruguez-Bolivar, 2017;Ubaldi, 2013). Researches on Web 2.0, social media, social networks and their use in the public sector show that issues such as the formation of social media and the role of social networks in public administration have been widely studied (Alguliyev & Yusifov, 2018;Kaur & Saini, 2016;Magro, 2012;Park et al, 2016). Key research areas include the role of social networks building a feedback between e-government and citizen, security issues establishing interactions with public authorities using social networks, transformation of social culture and management forms in the use of social media in egovernment.…”
Section: Role and Security Issues Of Social Network In E-governmentmentioning
confidence: 99%
“…Social networks have a significant impact on the performance of governments. For example, as a result of the survey, it has been shown that the impact of social media on the political activity of citizens and political participation is increasingly important (Grubmüller, Götsch, & Krieger, 2013;Kamiloglu & Erdogan, 2014;Park et al, 2016;Rainie et al, 2012). Experts note that social media will help governments to become more transparent by providing citizens with better service and access to information, by opening an active channel with them, and ultimately empowering citizens (Bertot, Jaeger & Grimes, 2010;Khasawneh & Abu-Shanab, 2013;Song & Lee, 2016).…”
Section: Role and Security Issues Of Social Network In E-governmentmentioning
confidence: 99%
“…Social media also provides unique opportunities for government organizations to make effective use of it to provide services to citizen's as per their desire and needs. Government organizations in different countries have started using social media to build closer ties with citizens and increase their participation in government services [5,6]. The statistics show that the usage of social media by governments across the world is increasing rapidly with the number more than three times from 2010 to 2012 and with another 50 per cent rise in 2014 [7].…”
Section: Introductionmentioning
confidence: 99%
“…Government organizations can integrate the information obtained from citizens into policy making and thus increase transparency through information sharing and collaboration with public to reach solutions for government problems. The citizens at the same time can get the opportunity to communicate and express their opinions on government policies and quality of services in real time environment [6]. The government use of social media is supported to strengthen citizen's interactivity [9], increase government transparency [10] and perception of trustworthiness [11].…”
Section: Introductionmentioning
confidence: 99%